2011
DOI: 10.1364/oe.19.004421
|View full text |Cite
|
Sign up to set email alerts
|

High power narrow-band fiber-based 
ASE source

Abstract: In this paper we describe a high power narrow-band amplified spontaneous emission (ASE) light source at 1030 nm center wavelength generated in an Yb-doped fiber-based experimental setup. By cutting a small region out of a broadband ASE spectrum using two fiber Bragg gratings a strongly constrained bandwidth of 12±2 pm (3.5±0.6 GHz) is formed. A two-stage high power fiber amplifier system is used to boost the output power up to 697 W with a measured beam quality of M2≤1.34. In an additional experiment we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Jin et al [20] demonstrated a 228 W thulium-doped all-fiber narrowband SFS at 1968.1 nm with a FWHM linewidth of 0.19 nm. Schmidt et al [21] presented a 697 W narrowband space-structured SFS at 1030 nm with a bandwidth of 12 pm by using two fiber Bragg gratings (FBGs) as wavelength selection component. In this Letter, we report a narrowband all-fiber MOPA structured SFS with maximal output power of 1.87 kW.…”
mentioning
confidence: 99%
“…Jin et al [20] demonstrated a 228 W thulium-doped all-fiber narrowband SFS at 1968.1 nm with a FWHM linewidth of 0.19 nm. Schmidt et al [21] presented a 697 W narrowband space-structured SFS at 1030 nm with a bandwidth of 12 pm by using two fiber Bragg gratings (FBGs) as wavelength selection component. In this Letter, we report a narrowband all-fiber MOPA structured SFS with maximal output power of 1.87 kW.…”
mentioning
confidence: 99%
“…To our understanding, so far the reported highest power achieved with narrow line-width from a fiber laser/amplifier at 1030 nm was no more than 700 W [6,7]. Although multi-kW CW output power centered at 1100 nm has been generated from fiber lasers recently [8,9], the line-widths are broad, more than 10 nm.…”
Section: Introductionmentioning
confidence: 96%
“…What is more, the presented high power SFSs in single-stage structure were often broadband and randomlypolarized [16][17][18][19] , while narrowband and polarization characteristics are required in practical applications [20,21] . Fortunately, employing master-oscillator-power-amplifier (MOPA) configuration can introduce a new horizon of high power SFS and leverage the high power SFS with special spectrum/polarization characteristics [22][23][24][25] and kilowatts operating power [26][27][28][29][30] . Besides, the output light of MOPAstructured SFS, in contrast to that of fiber MOPA seeded by standard resonant-cavity-based oscillator with self-pulsing effect, also has the advantages of high temporal stability [2,4] .…”
Section: Introductionmentioning
confidence: 99%